A comparison between Philips and Tomtec for left ventricular deformation and volume measurements in neonatal intensive care patients. Issue 3 (22nd December 2017) - de Waal, Koert; Phad, Nilkant
Abstract : Background: Two‐dimensional speckle tracking echocardiography is an emerging technique for analyzing cardiac function in newborns. Strain is a highly reliable and reproducible parameter, and reference values have been established for term and preterm newborns. Its implementation into clinical practice has been slow, partly due to lack of inter‐vendor consistency. Our aim was to compare recent versions of Philips and Tomtec speckle tracking software for deformation and semiautomated volume and area measurements in neonatal intensive care patients. Methods and results: Longitudinal and circumferential deformation and cavity dimensions (volume, area) were determined off line from apical and short‐axis images in 50 consecutive newborns with a median birthweight of 760 g (range 460–3200 g). Absolute mean endocardial global longitudinal strain measurements were similar between vendors, but with wide limits of agreement (Philips −18.9 [2.1]%, Tomtec −18.6 [2.5]%, bias −0.3 [1.7]%, and limits of agreement −3.6%–3.1%). Longitudinal strain rate and circumferential measurements showed poor correlation. All volume and area measurements correlated well between the vendors, but with significant bias. Conclusion: Global longitudinal strain measurements compared well between vendors but wide limits of agreement, suggesting that longitudinal measurements are preferred using similar hardware and software.